Wireless network based smart irrigation system using IOT - Kumar Verma, Ankit; K, Bhagavan; Akhil, Vamaraju; Singh, Amrita (International Journal of Engineering and Technology, 2017)
The Internet of things generally as IoT is a concept of sharing the network between different network objects through internet connectivity. The main objective of this project is to help the agriculturists during the irrigation process. IoT plays a major role in the grazing fields. The Smart irrigation system minimizes the wastage of water and helps farmers for successful usage of the water and besides the crop development. In the proposed paper we are describing an efficient system of irrigation to minimize the consumption of water in the. This in turn grants a remote control mechanism to monitor the process of irrigation. This irrigation process is automated only if the moisture, Temperature levels of the field falls below the reference value. The notifications that are retrieved by the sensor are sent to farmers mobile at a given period of time. The farmers can get SMS about the condition of the soil (whether soil is dry or wet) based the dryness of the soil. The farmers can easily operate the motor and can easily monitor all the operation in the fields. This intelligent Irrigation system’s efficiency is greater than 90% when compared with traditional method. Hence the designed system will provide the complete readings of the content of humidity in the soil and the timely records the temperature as well. This recorded data helps the farmers to inspect the proper functioning of the system and to supply the water into the field in the proper proportions.